Flight Mill Experiments and Computer Simulations Indicate Islands Recruit More Capable Flyers of Moths - Zheng, Yu-xuan; Wang, Ying; Dai, Bo-ya; Li, Zheng; Huo, Qi-run; Cui, Jian-xin; Liu, Hao; Li, Xin-hai; Hughes, Alice C.; Zhang, Ai-bing (Frontiers in Ecology and Evolution, 2021)
Understanding traits which relate to species colonization and invasability are key questions for both pest management and evolution. One key component is flight, which has been measured for a number of insect species through radar and tethered flight mill systems, but a general understanding of insect flight at the level of community is lacking. In this study, we used the flying mill system to quantify migration behavior of moth species, and the simulation method to study which moths in mainland China have the potential of cross-island dispersal. We found that moths from superfamily Geometroidea (family Geometridae) has the weakest flight ability among the seven Lepidoptera superfamilies, which is characterized by the shortest LSF (longest single flight), the shortest T_LSF (time corresponding to the longest single flight), the lowest TDF (total distance flown) and the lowest V_TDF (average speed during the flight). Surprisingly, family Pyralidae (superfamily Pyraloidea) has the highest flight endurance of all 186 species of 12 families in this study, with the longest LSF and T_LSF. The comparison between species common to mainland and islands shows that flight distance (LSF) may be more important for species spread than flight speed. The results of mainland-island simulations show that when P_((LSF>CD)) (the proportion of individuals whose LSF is greater than the closest distance between the mainland and island) is less than 0.004, it is difficult for moth species to disperse to or from islands without relying on external factors such as airflow.